DYNAMICS OF POLLUTANT EMISSIONS INTO THE ATMOSPHERIC AIR IN KYIV FROM MOBILE SOURCES OF POLLUTION - KHATSEI, ARSENII; TRUS, INNA (Herald of Khmelnytskyi National University. Technical sciences, 2025)
The study establishes that air pollution is one of the most significant environmental challenges for modern cities. Mobile pollution sources (automobile transport) are the primary factors degrading air quality in large cities, including Kyiv. According to the State Statistics Service of Ukraine (2023), the share of road transport in total pollutant emissions in Kyiv exceeds 85%. Major pollutants, such as nitrogen oxides (NOx), fine particulate matter (PM10, PM2.5), and carbon dioxide (CO2), pose serious health risks to the population and ecosystems. This study analyzes the key trends in changes in pollutant emissions into Kyiv’s atmospheric air from mobile sources. The dynamics of emission changes are examined. The findings reveal an increase in NOx and PM2.5 concentrations in densely populated districts with high traffic loads, especially during peak hours. Despite the introduction of stricter environmental norms for vehicles, the overall volume of emissions has not significantly decreased due to the growing number of private cars and insufficient implementation of eco-friendly transport policies. Additionally, air quality monitoring data indicate seasonal fluctuations in pollution levels, with the highest concentrations recorded during the winter months due to temperature inversions and reduced atmospheric dispersion. The dynamics of air pollution in Kyiv are critically important in the context of the city’s sustainable development. Within the framework of the European Green Deal and Ukraine’s integration into EU environmental standards, studying pollution trends and sources is essential for developing effective emission reduction measures. However, domestic statistics and monitoring methodologies often do not meet modern requirements, creating gaps in air quality management. In the context of Kyiv, the increasing number of cars per capita (a 20% rise over the past 10 years) further underscores the relevance of studying this issue. Recommendations have been proposed to reduce emissions by optimizing transport infrastructure, developing public transportation, introducing electric vehicles, and utilizing alternative fuel sources. The findings of this study may be useful for shaping the city’s environmental policy and improving air quality in Kyiv.